Canadian economic impact of improved workplace productivity in patients with major depressive disorder treated with vortioxetine. (23rd June 2020) - Lachaine, Jean; Beauchemin, Catherine; Bibeau, Joëlle; Patenaude, Julie; Chokka, Pratap; Proulx, Jean; Bougie, Joanna
Abstract : Objective: The AtWoRC study is an interventional, open-label Canadian study that demonstrated significant improvements in cognitive function and workplace productivity in patients with major depressive disorder (MDD) treated with vortioxetine for a current major depressive episode. The objective of the present analysis was to assess the Canadian economic impact of improved workplace productivity based on the AtWoRC study results. Methods: The economic impact of improved productivity in patients with MDD treated with vortioxetine was assessed over a 52-week period considering productivity loss due to absenteeism and presenteeism using the standard human capital approach and an employer's perspective. Absenteeism was measured with the Work Productivity and Activity Impairment questionnaire; and presenteeism with the Work Limitation Questionnaire. Productivity gains following treatment initiation with vortioxetine were estimated using the difference from baseline. Results: In the AtWoRC study, patients at baseline reportedly missed, in the past 7 days, an average of 8.1 h due to absenteeism and 3.0 h due to presenteeism. Following 52 weeks of treatment with vortioxetine, patients reportedly missed an average of 4.9 h due to absenteeism and 2.0 h due to presenteeism. This improved workplace productivity translated into savings of C110.64 for 1 week of work following 52 weeks of treatment. The cumulative 52-week economic impact showed potential savings of C4, 550 when factoring in the cost of therapy. Conclusion: This study suggested that workplace productivity gain due to an improvement in symptoms of MDD following treatment with vortioxetine will lead to substantial cost savings for the Canadian economy.